2012
DOI: 10.2176/nmc.52.816
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Hinge Technique for Head Trauma or Stroke

Abstract: Hinge technique is a new method for cerebral decompression that allows the bone flap to move outward in response to brain swelling and essentially allows reconstruction of the cranial vault as a minor procedure under local anesthesia. This retrospective study assessed outcomes following the use of this new decompressive technique. During an approximately 7-year period (June 2004 to March 2011), 58 patients who had suffered head trauma or stroke underwent cerebral decompression using the hinge technique or conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Infection Many studies reported bone flap or prosthesis infection [10, 20, 29, 36, 38, 43, 71, 91, 109, 125, 132, 135, 136, 139, 140, 148151]. These infections were encountered in 5.4 % (164/3056) of adult patients and 6.1 % (6/99) of pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…Infection Many studies reported bone flap or prosthesis infection [10, 20, 29, 36, 38, 43, 71, 91, 109, 125, 132, 135, 136, 139, 140, 148151]. These infections were encountered in 5.4 % (164/3056) of adult patients and 6.1 % (6/99) of pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…International consensus guidelines concerning decompressive craniectomy in the management of patients with TBI were recently published. 24 Future potential modifications of the craniectomy surgery technique are unlikely to change our results: hinged craniotomy, [25][26][27] unilateral craniectomy, or even not opening the dura at all are strategies that limit brain herniation, but were not tested in the DECRA trial. DECRA excluded patients with intracranial hematomas (mass lesions) as these patients often require craniectomy to evacuate hemorrhage, and it also did not include patients with penetrating gunshot or blast craniocerebral injury.…”
Section: Twelve-month Outcomes Of Craniectomy Rctmentioning
confidence: 96%
“…Tsermoulas et al [25] also found that more patients in the DC group had poor functional status at 6 months compared with the HC group at 6 months (HC n = 6, 35%; DC n = 41, 59%). On the contrary, Kano et al [23] compared DC with hinge craniotomy following TBI or stroke and found no significant difference in the long-term functional outcome, as measured by post-operative GOS and mRS. There were variable lengths of follow-up, if at all stated.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…A total of 15 studies [10][11][12][13][18][19][20][21][22][23][24][25][26][27][28] were eligible for inclusion ( Fig. 1), comprising 283 patients with a mean age 45.1 years and a male:female of 199:46 ( Table 1).…”
Section: Indication and Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation